Streptococcus gallolyticus subspecies pasteurianus causing late onset neonatal sepsis and meningitis: a case report - Saifullah, Khalid M.; Ranjan, Ankit; Kumar, Rajesh; Ansari, M. Tasawar (International Journal of Contemporary Pediatrics, 2024)
Streptococcus gallolyticus is a gram-positive microbe rarely isolated from cases of neonatal sepsis. Prompt identification, management and monitoring is necessary in such cases due to potential complications like meningitis and endocarditis. We report a preterm baby referred to us on day 18 of life with fever, respiratory distress and lethargy with seizure. Blood culture revealed S. gallolyticus subspecies pasteurianus with meningitis on cerebrospinal fluid examination. He was treated with 21 days of injectable vancomycin and teicoplanin. Baby had no neurological sequelae or other end organ complications. To the best of our knowledge, this is the first case report from eastern India describing sepsis secondary to this rare organism.